Bicorporates. Studies in Revivals and Migrations of Art Motifs - Slomann, Vilhelm (1967)
Two volumes; Prolegomena: I. Bicorporates and their Treatment in Art History; II. Seals and Bicorporates; III. Bicorporate Sphinxes. Book I: Motifs and Details: I. The Hov Font; The Hov Family; III. The “Tail-hold”; IV. Types of Bicorporates; V. Characteristic Details; VI. Postures and Movements; VII. Contortion; VIII. Peripheral Examples of Motifs and Details. Book II: I. Origins; II. Revivals in the European Art Tradition; Revivals in the Pre-islamic East; IV. Revivals in the Near East; V. Migrations to India; VI. Westward Migrations; VII. Migration of Art Motifs in the 11th and 12th Centuries; D.kr. 400; Wiederaufnahme mesopotamischer Motive in der romanischen Kunst; Vermittlung durch die Kreuzzüge.